2022
DOI: 10.1155/2022/8479940
|View full text |Cite|
|
Sign up to set email alerts
|

Music Art Teaching Quality Evaluation System Based on Convolutional Neural Network

Abstract: With the rapid growth of music and art education in colleges and universities today, the development of associated teaching quality assessment (TQE) is still in its infancy. In truth, most modern music and art education has yet to build a rigorous and appropriate evaluation system based on actual classroom teaching quality. Simply adopting classroom TQE indicators and approaches from other disciplines would unavoidably lead to formalization of music TQE findings in some schools and institutions. It has no bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It has no bearing on evaluation, feedback, or advancement. Terefore, the superior performance of neural network is used [19] to solve nonlinear problems and construct a music art TQE method based on convolutional neural network (CNN) while other infuential works are discussed in [20].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has no bearing on evaluation, feedback, or advancement. Terefore, the superior performance of neural network is used [19] to solve nonlinear problems and construct a music art TQE method based on convolutional neural network (CNN) while other infuential works are discussed in [20].…”
Section: Related Workmentioning
confidence: 99%
“…In the past, traditional machine learning often used manual extraction of target features for model training [16,20]. In the feld of music, it mainly used basic data such as loudness, frequency, and beat.…”
Section: Application Of Grey Neural Network In Music Artmentioning
confidence: 99%
“…These parameters serve as inputs to the BP neural network, providing the data necessary for analysis and evaluation. Next, data collection and preprocessing are essential steps to ensure the quality and reliability of the input data [14]. This may involve gathering academic records, survey responses, performance evaluations, and other relevant information from various sources within the college ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%